ECONOMIC AND MANAGEMENT ISSUES CONCERNING ARCHAEOLOGICAL SITES: COST ANALYSIS, STUDY OF TOURIST FLOWS AND SUSTAINABILITY PERSPECTIVES FOR THE ARCHAEOLOGICAL PARK OF POMPEII - Gabriel Zuchtriegel; Luigi Petti; Antonio Nesticò; Gabriella Maselli; Vincenzo Calvanese; Anna Onesti; Arianna Spinosa (Valori e Valutazioni)
The efficient allocation of the resources available to an archaeological park is particularly important in relation to excavation, restoration and conservation activities. These are generally very extensive and complex spheres, which require significant effort and high levels of expertise to maximise the social, cultural and economic benefits for the entire neighbouring area. Within a methodological framework aimed at outlining the theoretical approaches designed to assess the sustainability (including economic sustainability) of investment projects for archaeological parks, this article begins by outlining a general model for the analysis and selection of project initiatives. The model is then applied to a real-life case of international significance, the Archaeological Park of Pompeii, whose most recent experiences have prompted this study, with the aim of deriving: parametric data on the costs of excavation, restoration and conservation; information on the temporal evolution of the site’s attractiveness to tourists; initial indications regarding the sustainability of new excavations in the ancient city and the surrounding area. The result is both cost values which are useful for experts in the field and sustainability perspectives which can help public operators in decision-making processes.